An approach to computational fluid dynamic air-flow simulation in the internal combustion engine intake manifold - Galambos, Stjepan; Nikolic, Nebojsa; Ruzic, Dragan; Doric, Jovan (Thermal science, 2020)
The subject of this paper is modeling of an intake manifold of a four-stroke IC engine using contemporary software tools. Virtual 3D CAD model of an intake manifold was designed based on a real intake manifold of a four-stroke IC engine. Based on the CAD model a 3D CFD model of the intake manifold was created. The modeling has been done with the purpose of simulation of the air flow inside the intake manifold in order to monitor values of the internal pressure during several seconds of the engine operation in three different operating points. Also, an experiment was conducted, which included measurements of intake manifold pressure in the same engine operating points in the course of a time interval of approximately the same duration. The results of both the simulation and the experimental measurements have been shown in the paper proving that the created model was good enough for the intended purpose. nema